Determining Composition of Volatiles in Couroupita guianensis Aubl. Through Headspace-Solid Phase Micro-Extraction (HS-SPME) - Arpita Mandal Khan; K S Shivashankara; T K Roy (Journal of Horticultural Sciences, 2014)
Composition of volatile components in Couroupita guianensis Aubl. flowers was analyzed using headspace-solid phase micro-extraction (HS-SPME), followed by capillary gas chromatography and mass spectrometry (GC-MS) separation and identification. In all, 75 compounds were identified accounting for 96.32% of the total volatiles present. The major groups of compounds present were oxygenated terpenoids (35.66%), alcohols (26.92%), esters (17.36%), mono-and sesqui-terpenoids (8.64%), aldehydes and ketones (4.71%), hydrocarbons (1.68%), phenols (0.18%), acids (0.754%) and heterocyclic compounds (0.42%) constituted a small proportion of the volatile profile. The most abundant individual constituent was eugenol (18.95%) followed by nerol (13.49%), (E,E) farnesol (12.88%), (E,E)-farnesyl acetate (6.68%), trans ocimene (6.02%), nootkatone (4.64%), geraniol (2.94%), 2-isopropenyl-5- methyl-4-hexenyl acetate (2.69%), cedr-8-en-13-ol (2.58%), (E,Z)-farnesyl acetate (2.40%) and methyl (11E)-11- hexadecenoate (2.041%). Analytical comparison of composition of volatiles in the flowers, obtained by different methods of extraction, viz., solvent extraction, micro-simultaneous extraction and headspace-solid phase microextraction, revealed specific variations in relative concentrations of the constituent chemicals. Linalool was the major chemical (21.5% and 14.9%) in solvent extract and micro-simultaneous extract, respectively, but appeared in negligible quantity (0.16%) in head-space analysis.